The key reasons for dropout in Slovenian music schools – a qualitative study - Kavčič Pucihar, Ana; Habe, Katarina; Rotar Pance, Branka; Laure, Maruša (Frontiers in Psychology, 2024)
Music education often struggles to sustain students' long-term commitment, with many perceiving lessons as frustrating or unengaging, leading to discontinuation. To address this gap, our study aimed to elucidate the primary reasons for dropout from the perspectives of various stakeholders, including students, parents, teachers, and principals. Drawing upon the self-determination theory, our research comprehensively investigated internal and external factors contributing to dropout rates. Our findings highlighted the critical role of autonomy, competency, and relatedness in shaping students' decisions to continue or discontinue music education. We observed that inadequate teacher-student relationships, limited peer interactions, and uninspiring classroom atmospheres significantly impacted dropout rates. Moreover, challenges in the music school curriculum, such as difficulties with music theory and solfège, resource limitations, and excessive workloads, emerged as prominent barriers to student engagement. By addressing these multifaceted issues, our study underscores the importance of fostering supportive environments that cater to individual needs and interests, ultimately enhancing the overall music education experience and reducing dropout rates. This research represents the first systematic empirical study in Slovenian music education, laying the groundwork for future quantitative investigations to advance education practices in Slovenia.